Evaluation of corneal epithelial mapping in type-2 diabetes mellitus - Esraa R. Hassaan; Mostafa M. Bahgat; Ahmed F. El-Shahed (Journal of the Egyptian Ophthalmological Society)
Aim To quantify corneal epithelial changes in type-2 diabetic patients (DM-2) using anterior-segment optical coherence tomography (AS-OCT). Setting BADR University Hospital, and Al-Mashreq Eye Center, Cairo, Egypt. Patients and methods A prospective, comparative study that included, total 96 eyes: 48 eyes of 24 DM-2 patients, and 48 eyes of 24 healthy participants. Diabetic cases were sub-divided into controlled, and uncontrolled groups. All participants were recruited and underwent standard clinical examination and testing including history taking, a detailed ophthalmic examination, and lab investigation. AS-OCT was used to evaluate corneal epithelial thickness (using OptoVue, AS-OCT). Results The mean duration of diabetes in all studied patients was 16.1±6.9 (0.17–30) years. There were 16 (66.7%) controlled patients and eight (33.3%) uncontrolled patients in the patient’s group. Clinical data showed a high statistically significant (P<0.001) decreased best-corrected visual acuity in patient’s group. No statistically significant difference (P=0.979) between studied groups as regards intraocular pressure. At 5 mm zone, the patient’s group showed a high statistically significant (P<0.001) decrease in superior corneal epithelium and superio-temporal corneal epithelium. Also, there was a statistically significant decrease in temporal corneal epithelium (P=0.008), and superio-nasal corneal epithelium (P=0.019). While at 7 mm zone, high statistically significant (P<0.001) decrease in superior, Superio-temporal, inferior, and Infero-nasal corneal epithelium in patient’s group. Also, a statistically significant decrease in temporal corneal epithelium (P=0.017) and superio-nasal corneal epithelium (P=0.002) was noted in patient’s group. In the patient’s group, there was no statistically significant (P>0.05) correlation between DM duration and corneal epithelial mapping in both 5 mm and 7 mm. no statistically significant (P>0.05) correlation between DM severity and corneal epithelial mapping, however there was a statistically significant (P=0.008) decreased corneal epithelium in uncontrolled patients in infero-nasal cornea (P=0.008), and Infero-temporal cornea (P=0.041) at 7 mm zone. Conclusion AS-OCT is a noninvasive and highly effective procedure in early detection of corneal epithelium abnormalities. DM-2 has a significant effect on the corneal epithelial thickness.